Examining the Relationship Between Victimization, Psychopathy, and the Acceptance of Rape Myths - Cooke, Eric M. (Journal of interpersonal violence, 2022)
Rape myths are attitudes that implicitly and explicitly blame victims for their own sexual victimization. Greater adherence to rape myths is linked to several negative outcomes, including the neutralization of gender-based violence and the perpetration of sexual violence. Few studies have considered how previous life experiences and individual-level traits influence the development and greater adherence to rape myths. The current study examines how traits associated with the three-factor model of psychopathy (i.e., egocentric, callous, and antisocial dimensions) and adherence to traditional gender roles mediate the relationship between prior childhood/adolescent victimization and the acceptance of rape myths in a sample of college men and women (N = 789). Path modeling indicates that experiences of psychological victimization (before age 16) increased egocentric psychopathic traits, which then increased the acceptance of rape myths in men. In women, however, sexual victimization (before age 16) increased the acceptance of traditional gender roles, which then influenced the acceptance of rape myths. Additionally, the egocentric facet of psychopathy exerted indirect effects on the acceptance of rape myths through traditional views on gender roles in both men and women. These findings highlight the need to continue to examine egocentric personality traits in relation to the development of rape myths in adolescent and young adult populations. Directions for collegiate programming are discussed.